The Impact of Packed Classrooms on Teaching and Learning in Elementary Schools of Quetta - Naseer Ahmed; Ume Kalsoom; Wadana Tareen; Khushbakht Tareen; Spozmi Rahim (Dialogue Social Science Review (DSSR), 2025)
Overcrowding in classrooms will be a serious problem in Pakistan. Also taken into account as a contributing cause to the decline in educational standards. In Quetta City's public sector schools, this study aims to look into the "effect of overcrowded classrooms on Teaching-learning process at the basic level." What factors are produced by the crowded classroom? These are the questions that encouraged the researcher to look into the issue. How does a packed classroom impact teaching and learning? How can the problems caused by packed classrooms be solved? 260 instructors and kids from 20 chosen primary schools in Quetta city made up the population. They were both male and female. The mix method strategy was applied. Both quantitative and qualitative data were gathered through concentrated group discussions and organised questionnaires.